1992
DOI: 10.1210/jcem.75.1.1619003
|View full text |Cite
|
Sign up to set email alerts
|

Intact parathyroid hormone overestimates the presence and severity of parathyroid-mediated osseous abnormalities in uremia.

Abstract: To examine the possibility that uremia alters the relationship between bioactive PTH serum concentrations and its osseous end-organ response, we evaluated the relationship between circulating intact PTH and bone turnover in 39 end-stage renal disease patients with hyperparathyroid-mediated bone disease of varying severity. We excluded from analysis patients with coexistent defects in mineralization to insure that bone remodeling indices primarily reflected the effects of PTH. The distribution of serum PTH leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
105
0
1

Year Published

1995
1995
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(106 citation statements)
references
References 19 publications
0
105
0
1
Order By: Relevance
“…The PTH levels in the range 150-300 pg mL − 1 are currently recommended as target levels in the dialysis population [12,52] . Former studies showed varying correlations between PTH levels and bone histology (0·96 -0·85).…”
Section: Parathormon (Pth)mentioning
confidence: 99%
“…The PTH levels in the range 150-300 pg mL − 1 are currently recommended as target levels in the dialysis population [12,52] . Former studies showed varying correlations between PTH levels and bone histology (0·96 -0·85).…”
Section: Parathormon (Pth)mentioning
confidence: 99%
“…Outros fatores, como a alteração do metabolismo da vitamina D, hiperfosfatemia, acidose (54) e redução na expressão do receptor do PTH (55) contribuem para a dessensibilização do esqueleto à ação do hormônio. Assim, níveis de PTH 2 a 4 vezes o limite superior do valor de referência são considerados adequados em pacientes com IRC moderada a grave (56,57). Em pacientes em hemodiálise, a histologia óssea tende a estar pouco alterada quando os valores do PTH estão 2 a 3 vezes elevados (56)(57)(58).…”
Section: Indicações Não-clássicasunclassified
“…They were matched for gender, age and length on dialysis to a group of patients with serum PTH concentration between 64 and 290 pg/ml (control group; N = 16). According to some studies, normal bone metabolism in chronic renal failure has been associated with PTH levels up to 4 times the upper normal limit (20,21). None of the patients in the control group had ever been treated for secondary hyperparathyroidism.…”
Section: Patientsmentioning
confidence: 99%